THE INFLUENCE OF SELF-AWARENESS, HAPPINESS AT WORK AND PHYSICAL WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE AT BPKP SUMATETA UTARA - Victoria Via Dolorosa Situmorang; Ritha F. Dalimunthe; Sukaria Sinulingga (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
The importance of examining employee performance is because government institutions must be effective so that goals are achieved both in quality and quantity. Low performance causes a government institution or organization to experience losses which can then damage the quality of a government institution (Paais, 2018). Problems that occur with employee performance, government institutions need a role in management with Human Resources (HR) management to be able to maintain and improve better performance. Therefore, employee performance is important for government institutions. An employee who has high performance can encourage the achievement of government agency goals. There are many supporting factors that cause a decline in performance, namely self-awareness, happiness at work and the physical work environment and job satisfaction. This research aims to determine the influence of self-awareness, happiness at work and the physical work environment on employee performance, mediated by job satisfaction. This research was conducted on all auditors at BPKP Provincial Province, totaling 140 people. Data analysis used in this research is the outer model and inner model with SmartPLS software. The research results show that self-awareness, happiness at work and the physical work environment influence employee performance. Self awareness, happiness at work and the physical work environment influence job satisfaction. Self-awareness, happiness at work and the physical work environment influence employee performance, mediated by job satisfaction.